KEMAMPUAN BERPIKIR KRITIS DAN KETERAMPILAN PROSES DALAM PEMBELAJARAN SIKLUS BELAJAR 7E BERBASIS KEARIFAN LOKAL - Dewi, Ni Putu Sri Ratna; Wibawa, I Made Citra; Devi, Ni Luh Pande Latria (JPI (Jurnal Pendidikan Indonesia), 2017)
The purpose of this study was to determine differences in the ability of critical thinking and process skills among groups of students that learned the 7E learning cycle model based on local wisdom with students that learned kolompok conventional learning models. Significance pembelajran research related to science in primary schools is focused on memorization and rarely train high-level thinking skills of students, making it less in line with the purpose of learning science. The population of as many as 71 people, while the samples used were 58 people. The study design using pretest-posttes Control Group Design. Instrument in this research is to test the ability of critical thinking, and process skills test students. Data were analyzed by using MANOVA. The results showed there were differences in the ability of critical thinking and process skills significantly between students that learned with the learning cycle model 7E based on local wisdom and that learned to conventional models.